Effect of dielectric properties and elastic strain behavior on x/65/35 PLZT ceramics in lanthanum (x) ions contents - Ladapak Chumprasert (2018)
In this paper the effect of lanthanum addition on the phase formation, dielectric and ferroelectric characteristics of x/65/35 PLZT. This ceramics were prepared using mixed-oxide synthetic route via a rapid vibro-milling method. All samples were sintered at 1200°C for 12 h. X-ray diffraction was used to observe the crystal structure. It was found that when increasing lanthanum content, the structure remained rhombohedral. It can be seen that the change of behavior to ferroelectric relaxor with the increasing of lanthanum content resulted in the change of elastic strain. © (2014) Trans Tech Publications, Switzerland.